If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -18) + (7x + -31) = (13x + -9) + (19x + -6) Reorder the terms: (-18 + 8x) + (7x + -31) = (13x + -9) + (19x + -6) Remove parenthesis around (-18 + 8x) -18 + 8x + (7x + -31) = (13x + -9) + (19x + -6) Reorder the terms: -18 + 8x + (-31 + 7x) = (13x + -9) + (19x + -6) Remove parenthesis around (-31 + 7x) -18 + 8x + -31 + 7x = (13x + -9) + (19x + -6) Reorder the terms: -18 + -31 + 8x + 7x = (13x + -9) + (19x + -6) Combine like terms: -18 + -31 = -49 -49 + 8x + 7x = (13x + -9) + (19x + -6) Combine like terms: 8x + 7x = 15x -49 + 15x = (13x + -9) + (19x + -6) Reorder the terms: -49 + 15x = (-9 + 13x) + (19x + -6) Remove parenthesis around (-9 + 13x) -49 + 15x = -9 + 13x + (19x + -6) Reorder the terms: -49 + 15x = -9 + 13x + (-6 + 19x) Remove parenthesis around (-6 + 19x) -49 + 15x = -9 + 13x + -6 + 19x Reorder the terms: -49 + 15x = -9 + -6 + 13x + 19x Combine like terms: -9 + -6 = -15 -49 + 15x = -15 + 13x + 19x Combine like terms: 13x + 19x = 32x -49 + 15x = -15 + 32x Solving -49 + 15x = -15 + 32x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32x' to each side of the equation. -49 + 15x + -32x = -15 + 32x + -32x Combine like terms: 15x + -32x = -17x -49 + -17x = -15 + 32x + -32x Combine like terms: 32x + -32x = 0 -49 + -17x = -15 + 0 -49 + -17x = -15 Add '49' to each side of the equation. -49 + 49 + -17x = -15 + 49 Combine like terms: -49 + 49 = 0 0 + -17x = -15 + 49 -17x = -15 + 49 Combine like terms: -15 + 49 = 34 -17x = 34 Divide each side by '-17'. x = -2 Simplifying x = -2
| 12z-9-10z+3-8=z-9+3z+10-10z | | 8x+2x-3x-2x= | | 8x+1=23 | | 5m-10n=2 | | 3a+6b+3c= | | 8x=10+x | | -n-2u=5-n | | 9x+14=-40 | | 15x-3y=-18 | | n/7=12/42 | | -5X-7Y=-70solvey | | (x+2)(x+3)=(x+7)(x-4) | | -5X-7y=-70 | | 3(t+2)+4(t-1)=72 | | 16+6z=-8 | | 3log^7x=9 | | -25y^2-60y+60= | | d/33 | | -109/3 | | F(x)=4x^2-24x+20 | | t/4-7=16 | | 6x+7=-48-5x | | x^2-2.8x=9 | | 3s-15=-15 | | 5x^2-9x-7=0 | | x/4=21/36 | | -8+5t=-6 | | 7+91x=52x+16 | | 40-2x=8-10x | | 1/2/5/4 | | 8m+6=28 | | 3x+100=8x-5 |